Management of Late Preterm and Term Neonates exposed to maternal Chorioamnionitis - Mitali Sahni; María E. Franco-Fuenmayor; Karen Shattuck (BMC, 2019)
Abstract Background Chorioamnionitis is a significant risk factor for early-onset neonatal sepsis. However, empiric antibiotic treatment is unnecessary for most asymptomatic newborns exposed to maternal chorioamnionitis (MC). The purpose of this study is to report the outcomes of asymptomatic neonates ≥35 weeks gestational age (GA) exposed to MC, who were managed without routine antibiotic administration and were clinically monitored while following complete blood cell counts (CBCs). Methods A retrospective chart review was performed on neonates with GA ≥ 35 weeks with MC during calendar year 2013. IT ratio (immature: total neutrophils) was considered suspicious if ≥0.3. The data were analyzed using independent sample T-tests. Results Among the 275 neonates with MC, 36 received antibiotics for possible sepsis. Twenty-one were treated with antibiotics for > 48 h for clinical signs of infection; only one infant had a positive blood culture. All 21 became symptomatic prior to initiating antibiotics. Six showed worsening of IT ratio. Thus empiric antibiotic administration was safely avoided in 87% of neonates with MC. 81.5% of the neonates had follow-up appointments within a few days and at two weeks of age within the hospital system. There were no readmissions for suspected sepsis. Conclusions In our patient population, using CBC indices and clinical observation to predict sepsis in neonates with MC appears safe and avoids the unnecessary use of antibiotics.